The Delta Medial Axis: A fast and robust algorithm for filtered skeleton extraction. (August 2016) - Marie, Romain; Labbani-Igbida, Ouiddad; Mouaddib, El Mustapha
Abstract: In this paper, we present the Delta Medial Axis (DMA), a quasi-linear algorithmic solution addressing several of the main concerns of discrete medial axes (MA) computation. First, its sensitivity to small shape perturbations is counterbalanced by a single parameter (delta), used in a pruning strategy that implicitly takes into account the local topology of the boundary. Second, the discrete nature of images is addressed by approximating the original MA definition in continuous space. Third, to allow real-time performances, a set of algorithmic optimizations is proposed. We compare our approach both qualitatively and quantitatively to recent state of the art solutions, and show that the DMA presents an excellent choice for a wide range of applications. Finally, to allow fast and efficient use of our algorithm, we propose the complete pseudo-code. Abstract : Highlights: The Delta Medial Axis, a fast and robust skeletonization algorithm is presented. It includes a pruning parameter which considers the local topology of the boundary. To allow real time performances, optimizations are introduced with complete pseudo-code. A complete comparative study with four recent state of the art algorithms is proposed.